REDEFINING BODY AND ITS AGENCY: A STUDY OF THE WOMEN CHARACTERS IN ALICE WALKER’S NOVEL, THE COLOUR PURPLE - Puja Sarmah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In patriarchal cultures, women internalize oppression, for regnant narrative schemas, themes and figurations provide the default templates for their self-portraits and self-narratives and thus impede women's agency. To describe a woman's relationship with her body means to create a setting and the possibility to grasp women’s narratives and body language as they engage in acts of resistance, as well as the marking of body and space. Thus this study redefines the body as "agent" and also explores the body as a primary site for the construction and performance of gender, specifically of femininity, with examples drawn from the novel, The Colour Purple by Alice Walker. Agentic skills bring women's voices into alignment with their individual identities and their lives. Accordingly, this novel provides women with their agency using which enriches women's self-knowledge, extends their emancipatory potentialities, and strengthens their ability both to define themselves in their own terms and to enact their identities.